The Multidisciplinary Management of Avulsed Teeth: A Case Report - Adriana Jesus Soares, Francisco Souza-Filho; Maíra Prado; Thiago Farias Lima; Alexandre Zaia; Francisco Souza-Filho (Iranian Association of Endodontists; Iranian Center for Endodontic Research, 2012)
This paper reports multidisciplinary treatment of a dental trauma case to achieve a favorable prognosis. A healthy 14-year-old girl reported avulsion of teeth 11 and 21 which had occurred three months earlier. The initial treatment consisting of replantation with a semi-rigid splint was performed in hospital. At presentation, the patient was still using the semi-rigid splint. The clinical examination revealed the presence of increased mobility in teeth 11 and 21, and absence of vitality in both. Radiographic examination showed the presence of inflammatory external root resorption in both teeth. The treatment proposed consisted of teeth extraction, a temporary prosthesis followed by adhesive prosthesis, and finally, implant surgery associated with porcelain crowns.